PENGARUH PEMBELAJARAN PENDEKATAN TAKTIS TERHADAP HASIL BELAJAR PERMAINAN HOKI DI SMK NURUL ISLAM CIANJUR : Studi Eksperimen Pada Siswa/Siswi Yang Mengikuti Ekstrakurikuler Hoki di SMK Nurul Islam Cianjur Tahun Ajaran 2017-2018 - Acep Luqmanul Hakim, - (2019)
This study aims to determine the effect of tactical approach learning on the learning outcomes of hockey games at SMK Nurul Islam Cianjur. The method used in this study is the experimental method with the design of one group free test post test. The population in this study were students of SMK Nurul Islam Cianjur, with a sample of 30 students participating in a hockey extracurricular activity at SMK Nurul Islam Cianjur. The instruments in this study refer to hockey assessment instruments called GPAI (Game Performance Analysis Instruments) which have been adapted and modified from Griffin (Sucipto, 2015) by focusing on three aspects, namely execution skills, decision making, and support. Statistical analysis used to determine the effect of tactical approaches to learning outcomes of hockey games in this study using a paired sample T-test. Criteria for testing the hypothesis in this study using a significant level α = 0.05 which if t_ (count)> t_table, then Ho is rejected. The results showed that t_ (count) (2,865)> t_table (1,697), then Ho was rejected, which means that there is a significant influence in the application of a tactical approach to the learning outcomes of hockey games at SMK Nurul Islam Cianjur. Based on the results of this study, researchers provide recommendations to teachers to further develop and master various approaches to hockey games so that the learning atmosphere becomes more varied and student learning outcomes increase.